Plant water relations of Elytropappus Rhinocerotis with specific reference to soil restrictions on growth - Vermeulen, Tarina (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2010.